Comparative study: how dry heating treatment and annealing influence the multi-structure, physicochemical properties and in vitro digestibility of black highland barley starch - Liu, Hang; Gao, Shanshan; Tian, Ge; Zhang, Si; Liu, Shuang (Frontiers in Nutrition, 2024)
In this study, comparative investigation on the effect of dry heating treatment (DHT) and annealing (ANN) on multi-structure, physicochemical properties and in vitro digestibility of black highland barley (BHB) starch was done. Results revealed that both DHT and ANN did not affect the "A"-type crystalline pattern and FT-IR spectroscopy of BHB starch, but changed the morphology, raised water absorption capacity and lowered viscosities. Compared to native starch, DHT-and ANN-modified samples had totally opposite alteration trends in amylose content, color characteristics, oil absorption capacity, gelatinization parameters and pasting temperature. These changes were positively related to treatment temperature and time for DHT-modified starches, while which were dependant on treatment duration for ANN-modified starches. Total in vitro hydrolysis rate and rapidly digestive starch content in starch markedly raised after DHT, whereas slowly digestive starch and RS levels decreased. Nevertheless, ANN significantly improved the hydrolyzation stability with treatment time prolonging, especially increased RS content and lowered RDS level. Therefore, this study identified both DHT and ANN were effective methods to alter the properties of BHB starch, and more importantly, they had distinguishing influence by different mechanisms, which would remind user to select appropriate means for physical starch modification based on different application purposes.